Addressing the Covid-19 Burden on Medical Education and Training: The Role of Telemedicine and Tele-Education During and Beyond the Pandemic - Sharma, Divyansh; Bhaskar, Sonu (Frontiers in Public Health, 2020)
Medical students are the future of sustainable health systems that are severely under pressure during COVID-19. The disruption in medical education and training has adversely impacted traditional medical education and medical students and is likely to have long-term implications beyond COVID-19. In this article, we present a comprehensive analysis of the existing structural and systemic challenges applicable to medical students and teaching/training programs and the impact of COVID-19 on medical students and education. Use of technologies such as telemedicine or remote education platforms can minimize increased mental health risks to this population. An overview of challenges during and beyond the COVID-19 pandemic are also discussed, and targeted recommendations to address acute and systemic issues in medical education and training are presented. During the transition from conventional in-person or classroom teaching to tele-delivery of educational programs, medical students have to navigate various social, economic and cultural factors which interfere with their personal and academic lives. This is especially relevant for those from vulnerable, underprivileged or minority backgrounds. Students from vulnerable backgrounds are influenced by environmental factors such as unemployment of themselves and family members, lack of or inequity in provision and access to educational technologies and remote delivery-platforms, and increased levels of mental health stressors due to prolonged isolation and self-quarantine measures. Technologies for remote education and training delivery as well as sustenance and increased delivery of general well-being and mental health services to medical students, especially to those at high-risk, are pivotal to our response to COVID-19 and beyond.